2000
DOI: 10.1002/1097-4652(200101)186:1<1::aid-jcp1012>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathways of cyclic nucleotide-induced inhibition of arterial smooth muscle cell proliferation

Abstract: Cyclic adenosine 3',5'-monophosphate (cAMP) and cyclic guanosine 3',5'-monophosphate (cGMP) are second messengers involved in the intracellular signal transduction of a wide variety of extracellular stimuli. These signals regulate many biological processes including cell proliferation, differentiation, migration, and apoptosis. Recently, significant progress has been achieved in the molecular basis underlying cyclic nucleotide regulation of cell proliferation. This review summarizes our knowledge of the signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(9 citation statements)
references
References 116 publications
(145 reference statements)
0
9
0
Order By: Relevance
“…The expression of B-Raf in cells is therefore thought to determine whether cyclic AMP will activate (Rap1) or inhibit (PKA) ERK signaling (5,27,35,39). In previous analyses of VSMCs, cyclic AMP was reported to reduce signaling through the Raf/MEK/ERK pathway (21,23,30). This likely reflects a low expression of B-Raf (24) and a predominance of a PKA-dependent inhib- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of B-Raf in cells is therefore thought to determine whether cyclic AMP will activate (Rap1) or inhibit (PKA) ERK signaling (5,27,35,39). In previous analyses of VSMCs, cyclic AMP was reported to reduce signaling through the Raf/MEK/ERK pathway (21,23,30). This likely reflects a low expression of B-Raf (24) and a predominance of a PKA-dependent inhib- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial derived relaxing factors, such as NO or prostacyclin (PGI2), relax blood vessels and inhibit the proliferation and migration of SMCs by increasing synthesis of the cyclic nucleotides cAMP or cGMP. In fact, cAMP and cGMP inhibit the proliferation of arterial SMCs [111], and elevation of cyclic nucleotides reduces neointimal formation after angioplasty in animal models. Oral administration for 3-21 days of milrinone (0.3-3.0 mg/kg), a bipyridine derivative that specifically inhibits PDE3, suppressed intimal thickening by up to 56% in a dose-and time-dependent manner in a mouse model of photochemically induced vascular injury [112].…”
Section: Vascular Diseasementioning
confidence: 99%
“…These signals regulate numerous fundamental biological processes, including gene expression, cell proliferation and differentiation, cellular migration, and apoptosis. 1,2 Cyclic nucleotides exert both pro-and anti-apoptotic actions depending on the cell type. Some investigators have reported that cAMP and cGMP analogs cause apoptosis, e.g.…”
Section: Introductionmentioning
confidence: 99%